Penempatan Sumber Daya Manusia Profesional Di Lembaga Pendidikan Islam - Rusman Rusman (TADARUS, 2016)
AbstractUnderstanding placement of human resources in an attempt to channel the ability of human resources as well as possible by way of placing human resources at the position or positions most suitable to obtain optimal performance. Or in other words can be defined as a human resource policy for determining the position or title of a person in an institution. System placement of human resources in an organization or institution before the placement of the existing human resources it should first be made of a planned deployment of human resources. The plan includes how the amount of labor required, where the workforce will be placed, terms of office must be met by the concerned human resources to be able to take that position.